Menghadapi Stres Akademik: Kontribusi Dukungan Teman Sebaya dan Konsep Diri pada Siswa SMP: Penelitian - Yulyanti Minarsih; Devi Marganing Tyas; Nela Herlina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of peer social support and self-concept on academic stress among students at SMP IT “X” Karawang. The research employed a non-probability sampling technique using purposive sampling, involving 100 respondents. Data were collected using the Educational Stress Scale for Adolescents (ESSA) developed by Sun, Duune, Hou, and Xu (2011), the Peer Social Support Scale based on aspects proposed by Sarafino (2011), and the Tennessee Self-Concept Scale (TSCS) developed by Fitss and Warren (1996). Prerequisite tests, including normality and linearity tests, indicated that the data were normally distributed and had a linear relationship. Partial test results (t-test) showed that peer social support had a significant effect on academic stress (p = 0.035 < 0.05), and self-concept also had a significant effect on academic stress (p = 0.002 < 0.05). Simultaneous testing (F-test) revealed that peer social support and self-concept together significantly influenced academic stress with a significance level of p = 0.000 < 0.05. Additional analysis using the coefficient of determination test showed that the two independent variables simultaneously contributed 18.4% to academic stress, while the remaining 81.6% was influenced by other factors such as self-efficacy, optimism, achievement motivation, and family social support. This study highlights the importance of peer social support and self-concept in reducing academic stress among students and provides new insights for psychological interventions aimed at improving student well-being in the school environment.Abstract English version, written using Time New Roman-10, italic. Abstract contains research aim/purpose, method, and reseach results; written in one paragraph, single space among rows, using past tense sentences.